NEUTROPHILIC MYOSITIS ASSOCIATED WITH PYODERMA GANGRENOSUM IN A BREAK-DANCER - Hisashi Tamiya; Hiromi Kobayashi; Kaori Hoshi; Yui Horiguchi; Kurooka Sadahiro; Akiko Naruse; Shigeto Yanagihara; Daisuke Tsuruta (Our Dermatology Online, 2013)
Neutrophilic myositis is an extremely rare condition, cases of which have been reported in association with neutrophilic dermatosis, inflammatory bowel disease and malignant hematological disease. The disorder is histologically characterized by a sterile infiltration of neutrophils throughout muscle, with necrosis of muscle fibres. We here report the case of a young male who also had associated pyoderma gangrenosum, and who presented with necrotizing fasciitis-like manifestations. In this case, although there were no other underlying disorders, compulsive exertional stress due to break-dancing was thought to be a precipitant. Debridement of the necrotic tissues combined with oral corticosteroid treatment was effective.